Examination of the Sentencing Framework and the Application of Concurrent Offences to Fuel Oil Counterfeiting in Downstream Business Activities - Inge Yuliana Liman; Hwian Christianto (CV. Social Politic Genius (SIGn), 2026)
Fuel oil counterfeiting in downstream petroleum and natural gas business activities constitutes an economic criminal offense involving several criminal acts. Such conduct disrupts the order of fuel oil trade, harms consumers, and reduces the effectiveness of state supervision over energy distribution. This study examines the sentencing framework for fuel oil counterfeiting and assesses the implications of criminal penalty adjustment policy for the effectiveness of sentencing within the national petroleum and natural gas legal regime. This study is normative juridical research employing a statutory and conceptual approach, with qualitative and prescriptive analyses. The findings show that Article 54 of Law Number 22 of 2001, whose criminal provision has been amended by Law Number 1 of 2026, remains the principal basis for sentencing in cases of fuel oil counterfeiting. The application of concurrent offenses must be constructed based on the conformity of criminal elements, legal subjects, and the facts of the case. The penalty adjustment creates a juridical problem because it changes the nature of the sanction from cumulative to alternative-cumulative and reduces the criminal fine to category V. This change may reduce the effectiveness of criminal fines, particularly against Business Entities or Permanent Establishments. This study recommends optimizing prosecutorial demands within the construction of concurrent offenses and enacting explicit sector-specific criminal provisions so that the maximum criminal fine remains proportionate to culpability, consequences, and the benefit obtained from the criminal offense.